2019
DOI: 10.1002/cam4.2781
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of distant metastases in 215 Merkel cell carcinoma patients: Implications for prognosis and surveillance

Abstract: Approximately one‐third of Merkel cell carcinoma (MCC) patients eventually develop distant metastatic disease. Little is known about whether the location of the primary lesion is predictive of initial distant metastatic site, or if survival likelihood differs depending on the metastatic site. Such data could inform imaging/surveillance practices and improve prognostic accuracy. Multivariate and competing‐risk analyses were performed on a cohort of 215 MCC patients with distant metastases, 31% of whom had two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 33 publications
3
42
0
13
Order By: Relevance
“…33 Distant LNs and intra-abdominal organs were most often the first sites of distant metastases in the present study, consistent with previous findings that these sites are frequently involved in metastatic MCC. 12,13,34 While we found that the lung (0%) and brain (3%) were rarely the first sites of distant spread, they may be subsequently involved in 30% and 13% of patients, respectively. 34 Understanding these patterns of metastasis may help to guide follow-up imaging strategies.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…33 Distant LNs and intra-abdominal organs were most often the first sites of distant metastases in the present study, consistent with previous findings that these sites are frequently involved in metastatic MCC. 12,13,34 While we found that the lung (0%) and brain (3%) were rarely the first sites of distant spread, they may be subsequently involved in 30% and 13% of patients, respectively. 34 Understanding these patterns of metastasis may help to guide follow-up imaging strategies.…”
Section: Discussionmentioning
confidence: 62%
“…[7][8][9][10][11] Distant metastasis also occurs frequently; institutional series demonstrate that approximately one-third of patients with MCC will eventually develop distant disease. 12,13 However, because of the relative infrequency of this disease, the timing and frequencies of regional and distant disease spread have not been well characterized, resulting in relatively vague baseline and surveillance imaging recommendations. The National Comprehensive Cancer Network guidelines propose that baseline imaging with computed tomography Meeting presentation: Accepted for poster presentation at the 2020 Society of Surgical Oncology International Conference on Surgical Cancer Care (not presented because of COVID-19 pandemic).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Primary sites of metastasis were distant lymph nodes (41%), liver (23%), bone (21%), pancreas (8%), and lung (7%). 11,12 Distant skin or body wall metastases were more common in patients with an upper-extremity primary site than any other primary site. 11,13 Clinically, MCC presents as a rapidly growing, firm, painless, pink or flesh-colored nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Though nonspecific on exam and histology, the patient's rash to the trunk and extremities was compatible with a pembrolizumab-mediated hypersensitivity irAE. 30–40% of patients treated with anti-PD-1 immunotherapy experience all-grade dermatologic irAEs, while the incidence of all-grade rash is 14–17% [ 7 , 8 ]. The usual onset of rash is after the second cycle of therapy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%